Efficacy of entomopathogenic nematodes in laboratory and field conditions of Cicer arietinum against cotton bollworm, Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) - Maqbool Ahmed Mengal; Salma Javed; Saima Majeed (Egyptian Journal of Biological Pest Control, 2024)
Abstract Background The chickpea Cicer arietinum (Fabaceae) field has suffered significant economic losses due to the presence of cotton bollworm, Helicoverpa armigera Hübner (Lepidoptera: Noctuidae). Attempts to control the larval population through chemical pesticides led to some reduction but also resulted in the development of resistance among the larvae. Consequently, the H. armigera population experienced a rapid resurgence in the field. Given the substantial losses caused by Helicoverpa larvae, there is now a growing interest in adopting eco-friendly methods for management. The application of biocontrol agents has emerged as a promising solution for effectively managing the infestation. Results In the laboratory experiment, the entomopathogenic nematodes (EPNs) Steinernema pakistanense NNRC-NB.14, S. balochiense NNRC-NB.23, and S. abbasi NNRC-NB.33 were evaluated for their infectivity and mortality effects on mature cotton bollworm at various concentrations. The study demonstrated that the highest mortality rates were achieved at a concentration of 250 infective juveniles (IJs) per larva after 72 h. Steinernema pakistanense and S. balochiense exhibited higher mortality rates (95–98%) compared to S. abbasi (77%) at higher application concentrations. The field trial results reinforced the laboratory findings, demonstrating a significant decrease in H. armigera larval populations when employing EPN strains, particularly NNRC-NB.14 and NNRC-NB.33, compared to NNRC-NB.23. Despite the initial applications showing relatively low mortality percentages, the most effective larval control occurred after the third application of EPNs. The field trials revealed that, following the third spray, mortality percentages significantly increased from the initial range of 20–32% to a more substantial 70–90%. This cumulative impact highlights the importance of multiple applications in achieving optimal pest control. Conclusion The findings of these studies highlight the promising potential of EPN as an eco-friendly and sustainable method for controlling the cotton bollworm. However, the successful implementation of EPN-based control strategies in agricultural systems requires careful consideration of factors such as nematode species selection, application methods, environmental conditions, and integration with other pest management practices. Further research is needed to optimize the efficacy and practicality of using EPN on a larger scale, addressing issues such as nematode production, formulation, and compatibility with existing farming practice.